Carbohydrate composition in breast milk and its effect on infant health - Berger, Paige K. (Curr Opin Clin Nutr Metab Care, 2020)
PURPOSE OF REVIEW: This narrative review presents the current state of available evidence regarding the role of breast milk carbohydrates on infant outcomes, with a primary focus on growth and body composition. RECENT FINDINGS: To date, there is a paucity of available data that exists in this realm. The current literature focuses on the role of two carbohydrate fractions in breast milk, and their relationships with infant outcomes in the first six months of life: oligosaccharides and fructose. A small but growing body of research indicates robust associations of both oligosaccharides and fructose in breast milk with infant weight and length, as well as bone, fat, and lean mass. There is also emerging evidence to support the role of these same carbohydrate fractions in breast milk in infant cognitive development. SUMMARY: The present state of the science suggests that oligosaccharides and fructose in breast milk play a role in infant growth and body composition and introduces intriguing associations of these two carbohydrate fractions with infant cognitive development as well.